Democracy in Africa is either a myth or a reality: an analysis of democracy and democratization in Africa, a case study of Zimbabwe - Majengwa, Lance (Midlands State University, 2019)
As popular and mostly craved for as the most special and responsive form of governance and best form of political setup, democracy has caused quite a problematic predicament and dilemma in Africa. Criticisms have been directed at Africa’s failure to fully comprehend democracy and its many tenets that have at most times been seen as undermined. Amongst the most crucial complaints by the International organizations and renowned International Criminal Court have been the underlying accusation of an African continent that is laden with Human rights abuses, constitutional bastardization and meaningless elections that are dominated and saliently characterized by political violence and rigging. Democracy at such a point has been also seen as a neo-colonial project by the African leaders who are more or less facing execution and most times feeling the biting tongue of the ruthless megaphone diplomacy of the West, criticizing and labelling them as Dictators and Autocrats, such a situation has made the Democratization Agenda slow up since it has already made enemies through its agents who are synonymous with writings such the whitemen’ burden. Culture and Pan Africanism as national extensions of the national feeling have created a resisting bedrock for democracy with much rejection linked to such. The unlimited and forceful penetration of the many actors such as media, pressure groups has been brutally massacred at the mercy of protecting the state. Notwithstanding is the upcoming and piercing clamour for Lesbian Gays Bi-sexual and Transgender rights that have rocked Uganda and Zimbabwe. In initial reality, democracy seemingly seems to be a cultural suitable phenomenon than a one size fit all. Political actors, citizens and the governments in Africa should align their democratic tendencies with culture in order to harness democracy for the better good. In the same regard governments should open the political space in order for other actors to contribute to political development and political growth of Mother Africa.